Secularizing Asceticism. Arnold Gehlen’s Philosophical Conception of the Good Life (Diametros, 2019)
Asceticism as a part of the good life is often discussed in the contemporary philosophy (Foucault, Agamben, Sloterdijk). The aim of this article is to analyze and criticize the encouragement to ascetic practices which was formulated by a German conservative sociologist and philosopher, Arnold Gehlen (1904-1976). In my text, I track the history of the philosophical concept of asceticism and describe Gehlen’s anthropological suggestion that ascetic practices should be actualized and secularized. The author of Der Mensch claimed that the return to asceticism can become an utopian answer to the imperatives of the consumer society. I analyze his distinction of three types of askesis as stimulans, disciplina and sacrificium. Subsequently, I criticize Gehlen’s belief that asceticism has not been secularized in the modern age by showing that he ignored the phenomenon of “wordly ascetiscism” described by Max Weber and his followers. In the final section, I point out some authoritarian and elitist moments in Gehlen’s image of asceticism and I suggest alternative possibilities of developing his intuitions.
Keywords: Arnold Gehlen; asceticism; secularization; philosophical anthropology; Max Weber; Michel Foucault